Knowledge of Millennial Generation Craftsmen About the Production Process of Ikat Weaving Small Industries in Troso Village, Pecangaan District, Jepara Regency - Pangestuti, Nevi Dhefinta; Hardati, Puji Hardati (Forum Ilmu Sosial, 2025)
The need for clothing continues to increase in line with the number ofhpopulation. Meeting clothing needs is linked to the existence of garment companies and industries that produce clothing. Small industries play a crucial role in driving economic growth, such as providing employment opportunities. One small industry operating in the garment sector is the Troso Ikat Weaving Small Industry.In the weaving production process, there are three production flows starting from input, process, and output. This study aims to determine the knowledge of the millennial generation in the weaving industry activities in Troso Village, Pecangaan District, Jepara Regency. This study uses a quantitative approach. The population in this study was 428 and the sample size was 90 millennial ikat weaving artisans. The sample collection method used was proportional area random sampling. The variable in this study was the level of knowledge of weaving artisans. The level of knowledge of weaving artisans in Troso Village is included in the high category of 78.89%. The high level of knowledge of small ikat weaving industry artisans is influenced by their level of education, age, and experience. Therefore, knowledge in small ikat weaving industry activities needs to be improved by participating in job training and empowerment held by the Jepara Regency Government.